سیدہ فاطمہ الزہرہ رضی اللہ تعالیٰ عنھا کے فضائل و کمالات واقعاتِ سیرت کی روشنی میں: The Virtues and Excellences of Sayyida Fatima Al-Zahra in the light of her biography - Dr. Abdul Raouf Usmani; Dr. Muhammad Inamullah; Muhammad Sanaullah (Al Manhal Research Journal, 2024)
The life of Rasoolullah ﷺ is auspicious for all Muslims. The lives of the trained Companions and Companions and the Ahl al-Bayt are a beacon for us. Hazrat Fatima al-Zahra, who is the daughter of Hazrat Muhammad ﷺ. Hazrat Fatima al-Zahra's style of speech and behavior were in accordance with the Messenger of Allah, may Allah bless him and grant him peace, Hazrat Fatima al-Zahra's life is a perfect example of education and order for the entire Muslim Ummah, especially women. She (R.A) had qualities like patience, gratitude, piety, shyness, truthfulness, obedience from which the Muslim Ummah can get guidance in every aspect of life. In Islam, the sayings and deeds of the Messenger of Allah (peace and blessings of Allah be upon him), the Ahl al-Bayt and the companions have exemplary importance. There is no precedent for this in any other religion or society. In this Article, in the light of Sira-ul-Nabi (SAW), there will be a research discussion on the virtues,excellences and position of Hazrat Fatima al-Zahra RA.